2020
DOI: 10.3390/toxins12020065
|View full text |Cite
|
Sign up to set email alerts
|

Tb1, a Neurotoxin from Tityus bahiensis Scorpion Venom, Induces Epileptic Seizures by Increasing Glutamate Release

Abstract: Here, we report the neurotoxic effects aroused by the intracerebral injection (in rats) of Tb1, which is a neurotoxin isolated from Tityus bahiensis scorpion venom. Biochemical analyses have demonstrated that this toxin is similar to the gamma toxin from T. serrulatus, which is a β-scorpion toxin that acts on sodium channels, causing the activation process to occur at more hyperpolarized membrane voltages. Male Wistar rats were stereotaxically implanted with intrahippocampal electrodes and cannulas for electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…Isolated toxins from Tb venom have not yet been fully characterized and their effects on the central nervous system (CNS) are poorly understood. Some studies have demonstrated that peripheral Tb crude venom injection causes electroencephalographic and behavioral alterations ( Nencioni et al, 2009 ); fractions of this venom cause similar alterations and neuronal loss ( Lourenço et al, 2002 ); and some isolated toxins, when directly injected into the hippocampus of rats, induce wet dog shake (WDS), myoclonus, epileptic discharges ( Ossanai et al, 2012 ) and increase in the intracerebral level of glutamate ( Beraldo Neto et al, 2020 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Isolated toxins from Tb venom have not yet been fully characterized and their effects on the central nervous system (CNS) are poorly understood. Some studies have demonstrated that peripheral Tb crude venom injection causes electroencephalographic and behavioral alterations ( Nencioni et al, 2009 ); fractions of this venom cause similar alterations and neuronal loss ( Lourenço et al, 2002 ); and some isolated toxins, when directly injected into the hippocampus of rats, induce wet dog shake (WDS), myoclonus, epileptic discharges ( Ossanai et al, 2012 ) and increase in the intracerebral level of glutamate ( Beraldo Neto et al, 2020 ).…”
mentioning
confidence: 99%
“…The coordinates (AP −5.3, L −4.0, V −2.0.) were established according to the Stereotaxic Atlas of Paxinos and Watson (1998) and the surgical method was performed according to previous works ( Beraldo Neto et al, 2020 ; Nencioni et al, 2009 ; Ossanai et al, 2012 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation